Development of ios app for photonics/electromagnetics simulations - Maran, Nivedha (2018)
Engineering electromagnetics has proven to be a tough module for many university students. According to a survey conducted, 67% of students think that engineering electromagnetics is the toughest core module that they have taken in their course. Core modules are modules that must be taken and thus, this puts the student in a tough spot. It was later found that the majority of the reason for the students to feel that this module is difficult is due to the fact that they find it hard to visualize the graphs that are involved. This ability to visualize is also known as spatial thinking. The graphs typically display electromagnetic waves and how various scenarios affect the way they move in the x, y and z axes. According to the survey conducted, this is why such a large percentage of students feel this way about this module. This final year project aims to address this issue. An astounding 84% of students have said that they use a mobile application during the semester to aid them in the modules they are taking. This shows that creating an application that would teach and reinforce the concepts of electromagnetism to the students is clearly advantageous. Establishing basic concepts, showing a visual of the electromagnetic waves and testing the student on their concepts all in the same application allows for better learning, without the need to go to different websites, worrying about compatibility with different devices; ie. website displaying the waves may not be displayed properly or at all on the mobile phone as the website is not mobile friendly. This brings about the need to create this mobile application, E-Squared.